Yuendumu, legacy of a longitudinal growth study in Central Australia - Brown, Tasman (University of Adelaide Press, 2011)
his book provides a comprehensive account of a unique pioneering longitudinal study of human growth that continues to contribute to our knowledge and raise new questions 60 years after it commenced. Although over 200 scientific publications have arisen from the study, this book describes, in a single volume, the key researchers involved, the Australian Aboriginal people from Yuendumu who participated in the study, and the main outcomes. The findings have provided new insights into how teeth function, as well as factors affecting oral health and physical growth. General readers, as well as students and researchers, will find much of interest in this volume.